Nickel-based alloys for manufacturing pipeline tubing

JP2023553255A5Active Publication Date: 2025-03-04APERAM
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023526408
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2020-10-30
Publication Date
2025-03-04
Estimated Expiration
2040-10-30

AI Technical Summary

Technical Problem

Existing pipeline tube materials and welding techniques fail to meet the mechanical strength, corrosion resistance, and weldability requirements for deep-sea offshore oil and gas transportation at high laying speeds and depths, particularly below 3,000 meters, leading to potential deformation and failure due to mechanical stress and corrosion.

Method used

A nickel-based alloy with specific composition ranges for chromium, molybdenum, tungsten, and other elements, along with controlled impurities, is used as a filler material for pipeline tubes, ensuring high yield strength, localized corrosion resistance, and improved weldability, suitable for deep-sea applications.

Benefits of technology

The alloy achieves yield strength greater than 500 MPa, KCV elasticity of 100 J/cm², and resistance to localized corrosion, enabling pipeline tubes to withstand deep-sea conditions and high laying speeds, with reduced hot cracking and improved mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention has the following composition by mass: 16.5%≦Cr≦25.0%; 11.0%≦Mo≦18.0%; 2.0%≦W≦7.0%; Fe≦1.0%; Mo+W≦-0.5×(Cr+Fe)+30%; Mo+W≧-0.5×(Cr+Fe)+25%; Ti+Ta≦0.80%; 0.01%≦Si≦0.75%; 0.01%≦Al≦0.35%; 0.01%≦Mn≦0.35%; Ca≦0.005%; Mg≦0.005%; Nb≦0.0 1%; 0.001%≦C≦0.05%; 0.001%≦N≦0.05%; S≦0.003%; P≦0.005%; optionally 0.0010%≦Rare Earths≦0.015%, wherein the silicon content is less than or equal to 0.25% in the presence of rare earths in amounts between 0.0010% and 0.015%, the remainder being nickel and unavoidable impurities resulting from processing, and the nickel content is greater than or equal to 54%.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to nickel alloys intended for use in the fields of petrochemicals and the extraction of petroleum products, and more specifically, as part of the manufacture of pipeline tubes for transporting gas or oil. [Background technology]

[0002] The development of gas and oil requires the laying of offshore pipelines. For productivity and economic profitability purposes, it is desirable for pipelines to be laid at a rate of approximately 2 km / day. Currently, there are three technologies that meet such productivity requirements: • S-lay technology: Typically, pipe sections 9m or 12m long are manufactured on land in units called spool bases, then transported by ship over the sea, and butt-welded horizontally on barges. The laying is called S-lay, reminiscent of the shape the tubes take before contacting the seabed. S-lay technology is suitable for seabeds less than 2,000m deep. • J-lay technology: J-lay technology is a more recent technology adapted for deep sea (2,000m to 4,000m). Pipe sections are welded together on a vertical barge (at a slight angle) above sea level, forming a J-shape before contacting the seabed. • R-lay technology: The most recent R-lay technology is for small-diameter tubes and is specifically for non-deep-water areas. The tube line is welded together on land, then wound onto wheels for transport at sea, and subsequently unwound from the wheels using a specialized barge. R-lay technology is the most efficient.

[0003] Such laying techniques place mechanical stress on the tubes, particularly the orbital welds between tube sections, especially under the influence of bending during laying and the weight of the tubes before contact with the seabed. Therefore, the tubes, especially the welds, must be designed to withstand such stress in order to avoid deformation of the tubes during the laying phase.

[0004] In addition to requirements regarding laying speed, it is also necessary to increase the laying depth in order to keep the buried structure usable. Laying depths can reach approximately 2,500m to 3,000m. Such increases in laying depth increase the mechanical stress on the tubes and therefore require the use of carbon steel with increasingly high mechanical properties.

[0005] The tube sections used are typically manufactured in a factory by rolling steel sheets and then longitudinally welding the steel edges with a steel filler wire using a MIG / MAG process, with their composition selected according to the grade of the steel sheet. The wall thickness of the tube sections is typically around 25 mm, and their diameters range from 25 cm to 130 cm.

[0006] According to alternative examples and depending on the application, the tube sections are manufactured by billet extrusion. The tube sections and the tubes obtained by orbital welding of the tube sections do not use any longitudinal welding in such cases (seamless tubes).

[0007] The mechanical strength of the pipe section, as specified according to the steel grade, is reproduced below in accordance with API Specification 5L for steel grades X56, X60, X65, X70, or X80 that can be used in the manufacture of the pipe section. The steel grade corresponds to the yield strength of the steel sheet in units of ksi.

[0008] [Table 1]

[0009] Steel grades X56, X60, X65, X70, or X80 are defined in the American Petroleum Institute's "API Specification 5L" document, 45th edition, December 2012.

[0010] When a tube section includes longitudinal welds, it is required during the manufacturing of the tube section to obtain welds with mechanical properties equal to or greater than those of the base plate steel (overmatch) so that the pipe section can be designed according to the laying conditions (S, J, R) and the type of line operation, for example, to determine the thickness of the pipe section and the grade of steel to be used.

[0011] For example, when tube sections are manufactured by billet extrusion without longitudinal welding ("seamless" technology), it is possible to omit the specifications required for longitudinal welding ("overmatch").

[0012] After the tube section is manufactured, the inner surface of the tube section, including any longitudinal welds, is coated with a coating layer by welding with a filler wire. The purpose of this coating operation is to ensure the corrosion resistance of the tube during the transport of more or less corrosive petroleum products. The internal coating is typically made of Inconel® 625 alloy. Inconel® 625 alloy has the following composition by mass: Cr: 20.0~23.0% Fe ≤ 5.0% Mo: 8.0~10.0% Nb+Ta: 3.15~4.15% C ≤ 0.10% Mn ≤ 0.50% Si ≤ 0.50% P ≤ 0.002% S ≤ 0.015% Al ≤ 0.40% Ti ≤ 0.40% Other elements ≤0.5%, The remainder consists of nickel and unavoidable impurities resulting from manufacturing, with Ni ≥ 58%.

[0013] Inconel® 625 alloy is specified in Table 1 of Specification AWS A5.14 / A5.14M: 2018 (Specification for Nickel and Nickel-Alloy Bare Welding Electrodes and Rods) under the name "Chemical composition requirements for Nickel and Nickel-Alloy Electrodes and Rods" and to the AWS classification reference ERNiCrMo-3 (number UNS N06625).

[0014] When tube sections are manufactured, they are transported on board and butt welded by orbital welding when the tubes are laid using one of the aforementioned techniques.

[0015] Regardless of the laying technique used, the butt welds (orbital) made between tube sections should withstand the bending stresses of the line during laying and the self-weight of the line before it contacts the seabed. Therefore, the mechanical strength of the orbital welds is very important to prevent welding deformations during the laying stage.

[0016] Generally, the following properties are required for orbital welding between pipe sections: - Overmatch: It is required to obtain an orbital weld with a mechanical strength greater than or equal to that of the base metal, i.e., the steel of the pipe section. As described above for the longitudinal welds of the pipe sections, overmatch is used to design the pipe according to the laying conditions (S, J, R) and the type of operation of the line without considering the welds, and is particularly used to define the thickness of the pipe and the grade of steel used. - Local corrosion resistance greater than or equal to the corrosion resistance of the coating on the inside of the pipe section, so that the pipe can be designed to meet requirements regarding local corrosion resistance without considering the presence of orbital welds.

[0017] Throughout this description, localized corrosion refers to corrosion that is likely to develop a pitting mechanism.

[0018] To satisfy all of the above requirements, the inventors propose to produce an orbital weld in which a root pass is made into the coating using Inconel® 625 alloy filler wire, and to complete the weld by filler pass using steel of the same grade as the base metal. Such a welding technique provides good mechanical properties as it ensures a certain continuity of the materials used. On the other hand, such welding is accompanied by significant problems of high-temperature cracking, and therefore weldability, related to the dilution of the Inconel® 625 alloy. Thus, such a solution is not entirely satisfactory. In particular, cracks that appear during welding must be repaired, incurring considerable additional costs. Furthermore, if the cracks are not repaired, they pose a risk of causing tube failure in operation.

[0019] The inventors have also proposed performing full welding using a single wire made of Inconel® 625 alloy. Such a welding solution is, in fact, economical. Furthermore, the welding does not cause any problems of hot cracking and provides corrosion resistance comparable to that of a coating. The welding is also widely used to weld tubes up to grade X56 or even X60. However, it is no longer suitable for higher steel grades (X65, X70, and X80). However, the aforementioned requirements, more specifically in terms of laying speed and depth, increasingly necessitate the use of steel of higher grades than grade X60, especially grade X65 steel or even grade X70 steel. [Prior art documents] [Non-patent literature]

[0020] [Non-Patent Document 1] The American Petroleum Institute, "API Specification 5L" document, 45th edition, December 2012. [Non-Patent Document 2] Under AWS classification reference ERNiCrMo-3 (UNS number N06625), the standard AWS A5.14 / A5.14M: 2018 (Specification for Nickel and Nickel-Alloy Bare Welding Electrodes and Rods) is titled "Chemical composition requirements for Nickel and Nickel-Alloy Electrodes and Rods". [Non-Patent Document 3] Standard NF EN ISO 148-1 (January 2011) [Non-Patent Document 4] European standard FD CEN ISO / TR 17641-3 (November 2005) [Non-Patent Document 5] American Petroleum Institute, API Specification 5L Document, 45th Edition, December 2012. [Non-Patent Document 6] Under AWS classification reference ERNiCrMo-4 (UNS number N10276), see AWS A5.14 / A5.14M: 2018 (Specification for Nickel and Nickel-Alloy bare Welding Electrodes and rods), titled "Chemical composition requirements for Nickel and Nickel-Alloy Electrodes and Rods". [Non-Patent Document 7] Under AWS classification reference ERNiCrMo-7 (UNS number N06455), the standard AWS A5.14 / A5.14M: 2018 (Specification for Nickel and Nickel-Alloy bare Welding Electrodes and rods) is titled "Chemical composition requirements for Nickel and Nickel-Alloy Electrodes and Rods". [Non-Patent Document 8] Under AWS classification reference ERNiCrMo-10 (UNS number N06022), see AWS A5.14 / A5.14M: 2018 (Specification for Nickel and Nickel-Alloy bare Welding Electrodes and rods) titled "Chemical composition requirements for Nickel and Nickel-Alloy Electrodes and Rods". [Non-Patent Document 9] ASTM B214-07 standard [Non-Patent Document 10] Standard NF EN ISO 6892-1 (December 2019) [Overview of the Initiative] [Problems that the invention aims to solve]

[0021] Therefore, the object of the present invention is to overcome the aforementioned drawbacks and provide an alloy that can be used as a filler material for manufacturing pipeline tubes that are intended for transporting oil or gas and are suitable for laying at a high rate of production, especially at about 2 km / day, in deep sea, offshore, and especially below a depth of about 3,000 m.

[0022] Laying tubes at depths below approximately 3,000 m and at high laying speeds requires the use of steel with very good mechanical properties. Preferably, with respect to the mechanical properties of the welded assembly, a yield strength Rp greater than or equal to 500 MPa is required. 0.2 And, 100 J / cm 2 To obtain a KCV elasticity greater than or equal to that of 550 MPa, advantageously, a yield strength RP greater than or equal to 550 MPa. 0.2 and / or 120 J / cm 2 It is required to obtain a KCV elasticity that is greater than or equal to that of the given value.

[0023] Furthermore, the use of tubes as pipelines for transporting oil or gas requires good corrosion resistance and good weldability of the filler material. More specifically, local corrosion resistance and weldability are required to be greater than or equal to those of Inconel® 625 alloy. [Means for solving the problem]

[0024] To achieve this objective, the present invention provides the following composition by mass: 16.5% ≤ Cr ≤ 25.0% 11.0% ≤ Mo ≤ 18.0% 2.0% ≤ W ≤ 7.0% Fe ≤ 1.0% Mo+W≦-0.5×(Cr+Fe)+30% Mo+W≧-0.5×(Cr+Fe)+25% Ti + Ta ≤ 0.80% 0.01% ≤ Si ≤ 0.75% 0.01% ≤ Al ≤ 0.35% 0.01% ≤ Mn ≤ 0.35% Ca ≤ 0.005% Mg ≤ 0.005% Nb ≤ 0.01% 0.001% ≤ C ≤ 0.05% 0.001% ≤ N ≤ 0.05% S ≤ 0.003% P ≤ 0.005% If necessary, 0.0010% ≤ rare earth elements ≤ 0.015% It has a silicon content of less than 0.25% or equal to 0.25% in the presence of rare earth elements with a content between 0.0010% and 0.015%. The remainder consists of nickel and unavoidable impurities arising from the manufacturing process, relating to alloys with a nickel content greater than or equal to 54%.

[0025] The alloy according to the present invention may include one or more of the following features, individually obtained or in any technically possible combination: - Iron content is less than or equal to 0.5% - The rare earth elements are selected from yttrium, cerium, and lanthanum, and mixtures thereof, and - The rare earth element is selected from yttrium, or a mixture of cerium and lanthanum.

[0026] The present invention further relates to a coated part comprising a substrate made of a base material and a coating made of an alloy according to any one of claims 1 to 4, wherein the base material is a metallic material, preferably carbon steel, for example, X56, X60, X65, or X70 steel.

[0027] According to a particular embodiment, the coated component is a tubular section.

[0028] The present invention further relates to a filler wire made of the above-mentioned alloy.

[0029] The present invention relates to a method for manufacturing the above-mentioned filler wire, comprising the following steps: - A process of supplying semi-finished products made from the aforementioned alloy, - A process of heating a semi-finished product to a high temperature in order to form an intermediate wire, - A process including a drawing step that converts an intermediate wire into a filler wire having a smaller diameter than that of the intermediate wire. This includes methods.

[0030] The present invention further relates to a welded assembly comprising at least two parts of a component, each of which is made of a base material, the parts of the component being joined together by welding beads obtained from the aforementioned filler wire, wherein the base material is selected from iron-nickel alloys such as Fe-9Ni, nickel alloys such as C-276, C-4 or 22, and carbon steel, such as X56, X60, X65, or X70 steel.

[0031] The welded assembly according to the present invention may further include one or more of the following features, either individually obtained or in any technically possible combination: - The welded assembly forms a tubular section, which includes sheet metal bent into the shape of a tube, and its longitudinal edges form a part of the component that is joined together by welding beads. - The tube section is provided with a coating made of the aforementioned alloy on at least a portion of its inner surface, preferably all of it, and - The welded assembly forms a tube comprising at least two tube sections, the tube sections forming parts of the component, with weld beads extending along the circumference of the tube, and the tube sections are preferably the aforementioned tube sections.

[0032] The present invention further relates to a method for manufacturing a welded assembly, comprising the step of welding together two parts of a component using the aforementioned filler wire, particularly by arc welding.

[0033] The assembly manufacturing method may further have one or more of the following features, depending on whether they are individually obtained or in any technically conceivable combination: - The welding process is a process of welding the longitudinal edges of the sheet metal together, and the welding is preferably a longitudinal butt weld, and - The method involves the following sequential steps before the welding process: - A process of supplying a first tube section and a second tube section, each extending along the vertical axis and made of a base material, - A step of positioning the first and second tube sections such that the longitudinal end of the first tube section is positioned to face the longitudinal end of the second tube section along the longitudinal axis of the first and second tube sections. Includes, The welding process involves welding together the two longitudinal ends facing the first and second tube sections, preferably by orbital butt welding.

[0034] The present invention further relates to a part or component made of the above-mentioned alloy, which is produced by additive manufacturing.

[0035] The additive manufacturing process, in more detail, uses a filler wire and / or powder made from the aforementioned alloy as filler material.

[0036] Additive manufacturing processes are processes that use, for example, electric arcs, laser beams, and / or electron beams as energy sources to melt the filler material.

[0037] For example, additive manufacturing processes include wire-arc, wire-laser, electron beam-wire processes, or hybrid additive manufacturing processes that combine wire-arc and laser-powder or wire-arc and wire-laser technologies.

[0038] The present invention further relates to a method for manufacturing a part or a portion of a part, comprising the step of manufacturing the part or the portion of a part by a metal addition process using a filler wire and / or powder made of the above-mentioned alloy as a filler material.

[0039] Additive manufacturing processes are processes that use, for example, electric arcs, laser beams, and / or electron beams as energy sources to melt the filler material.

[0040] For example, additive manufacturing processes include wire-arc, wire-laser, electron beam-wire processes, or hybrid additive manufacturing processes that combine wire-arc and laser-powder or wire-arc and wire-laser technologies.

[0041] The present invention further involves the use of the above-mentioned filler wire, - Iron-nickel alloys such as Fe-9Ni, nickel alloys such as C-276, C-4 or 22, or carbon steel, particularly X56, X60, X65 or X70 steel, as welding filler wire for welding together two parts of a component made from a base material, and / or - Made of a metal-based material, preferably carbon steel, such as X56, X60, X65, or X70 steel, as a hard-facing wire for producing a coating on a part or portion of a part, and / or - As a filler wire in the metal addition process, Regarding use.

[0042] The present invention further relates to metal powders made from the aforementioned alloys.

[0043] The present invention further relates to a method for producing metal powder made from the above-mentioned alloy.

[0044] The present invention will be better understood by reading the following description, which is given merely as an example, and by referring to the enclosed drawings. [Brief explanation of the drawing]

[0045] [Figure 1] This is a schematic cross-sectional view of a welded assembly according to the present invention. [Figure 2] This is a schematic perspective view of a tube section according to the present invention. [Figure 3] This is a schematic top view of sheet metal used when carrying out the process for manufacturing tube sections. [Figure 4] This is a schematic perspective view of a tube according to the present invention. [Figure 5] This is a schematic perspective view of a part coated according to the present invention. [Figure 6] This is a schematic perspective view of a part produced by additive manufacturing according to the present invention. [Modes for carrying out the invention]

[0046] Hereafter, all content will be expressed as a mass percentage.

[0047] The alloy according to the present invention has the following composition by mass: 16.5% ≤ Cr ≤ 25.0% 11.0% ≤ Mo ≤ 18.0% 2.0% ≤ W ≤ 7.0% Fe ≤ 1.0% Mo+W≦-0.5×(Cr+Fe)+30% Mo+W≧-0.5×(Cr+Fe)+25% Ti + Ta ≤ 0.80% 0.01% ≤ Si ≤ 0.75% 0.01% ≤ Al ≤ 0.35% 0.01% ≤ Mn ≤ 0.35% Ca ≤ 0.005% Mg ≤ 0.005% Nb ≤ 0.01% 0.001% ≤ C ≤ 0.05% 0.001% ≤ N ≤ 0.05% S ≤ 0.003% P ≤ 0.005% If necessary, 0.0010% ≤ rare earth elements ≤ 0.015% It has a silicon content of less than 0.25% or equal to less than 0.25% in the presence of rare earth elements with a silicon content between 0.0010% and 0.015%. The remainder consists of nickel or unavoidable impurities resulting from the manufacturing process, with a nickel content greater than or equal to 54%.

[0048] Unavoidable impurities arising from manufacturing refer to elements present in the raw materials used to produce the alloy or originating from the equipment used to produce the alloy, such as the refractory materials of the furnace. Such residual elements have no metallurgical effect on the alloy.

[0049] A nickel content greater than or equal to 54% by mass in the alloy provides good ductility and good resistance to stress corrosion in the base material.

[0050] Chromium, in content between 16.5% and 25.0% by mass, provides good resistance to generalized corrosion and improves the mechanical properties of the alloy. More specifically, the inventors found that when the chromium content is less than 16.5% by mass, the resistance to generalized corrosion is insufficient. Furthermore, chromium content higher than 25.0% by mass leads to precipitation of the σ phase, which is associated with loss of ductility and increased susceptibility to high-temperature cracking, and thus to degraded mechanical properties of the alloy.

[0051] Preferably, the chromium content is greater than or equal to 17.0% and less than or equal to 23.0%.

[0052] When present in a content between 11.0% and 18.0% by mass, molybdenum improves resistance to localized corrosion.

[0053] Furthermore, molybdenum significantly improves mechanical properties. The inventors have found that molybdenum content below 11.0% by mass results in insufficient resistance to local corrosion and poor mechanical properties, while molybdenum content above 18% leads to the precipitation of undesirable phases, resulting in loss of ductility and increased susceptibility to high-temperature cracking.

[0054] Preferably, the molybdenum content is greater than or equal to 11.5% and less than or equal to 16.5%.

[0055] The tungsten content is between 2.0% and 7.0% by mass. At such concentrations, tungsten also improves resistance to localized corrosion. Furthermore, tungsten improves mechanical properties. The inventors have found that tungsten content below 2.0% results in insufficient resistance to localized corrosion. Moreover, tungsten content above 7.0% leads to the precipitation of undesirable phases, resulting in loss of ductility and increased susceptibility to high-temperature cracking.

[0056] The iron content is less than or equal to 1.0 mass%. The addition of iron degrades resistance to generalized corrosion. An iron content of less than or equal to 1.0 mass% allows for the formation of alloys from scrap materials containing residual iron, resulting in reduced manufacturing costs. At content higher than 1.0 mass%, iron also enhances the precipitation of undesirable phases, resulting in loss of ductility and increased susceptibility to high-temperature cracking.

[0057] Preferably, the iron content is less than or equal to 0.5% by mass.

[0058] The combined titanium and tantalum content is less than or equal to 0.80 mass%. While titanium and tantalum present at the levels described in the claims significantly improve mechanical properties, their low solubility in Ni-Cr alloys causes the precipitation of undesirable phases. Therefore, the content of these elements must be limited to low levels. However, these elements contribute to the deoxidation of the alloy during manufacturing. The inventors have found that when Ti+Ta is greater than 0.80 mass%, the precipitation of undesirable phases is observed, resulting in loss of ductility and increased susceptibility to high-temperature cracking.

[0059] According to the present invention, Mo + W ≤ -0.5 × (Cr + Fe) + 30 mass%. The inventors have found that by satisfying the above relationship, the fracture energy KCV ≥ 100 J / cm² is particularly satisfied. 2 We observed that this led to obtaining satisfactory ductility, as expressed by the coefficient of friction, and good weldability, as expressed by a total crack length of less than or equal to 20 mm.

[0060] The destructive energy KCV is J / cm 2 It is expressed in units of kCV. The fracture energy kCV reflects the elasticity of the part. For example, it is determined by an elasticity test conducted at room temperature according to the standard NF EN ISO 148-1 (January 2011).

[0061] The crack length is determined, in particular, by the Varestraint test according to the European standard FD CEN ISO / TR 17641-3 (November 2005), under a 3.2% plastic deformation.

[0062] Furthermore, Mo+W≧-0.5×(Cr+Fe)+25 mass%. By satisfying the above relationship, the inventors have achieved satisfactory mechanical strength, particularly a yield strength Rp greater than or equal to 500 MPa. 0.2 I discovered that this leads to obtaining [something].

[0063] At the aforementioned levels, during alloy production, silicon and aluminum enhance deoxidation, while manganese enhances desulfurization.

[0064] The calcium and magnesium content in the alloy is limited to 0.005 mass% each so as not to degrade weldability. More specifically, the calcium and magnesium content is limited so as not to degrade the quality of the weld seam, particularly the formation of slag on the surface, which can lead to instability in the arc and liquid bath.

[0065] The niobium content is less than or equal to 0.01% by mass. The niobium content in the alloy is limited so as not to degrade its resistance to high-temperature cracking. In particular, niobium is strongly segregated within the resinous intercrystalline space, enhancing the precipitation of undesirable phases.

[0066] The alloy further contains carbon and nitrogen in content between 0.001 and 0.05 mass%. The carbon content is controlled to facilitate deoxidation during alloy production. Furthermore, the carbon and nitrogen ensure the purification of the microstructure through the precipitation of Ti-(C,N) carbonitrides, when titanium is added.

[0067] To improve resistance to high-temperature cracking, the S and P content is limited as much as possible. The aforementioned content is less than or equal to 0.003 mass% and 0.005 mass% in the alloy described above.

[0068] If necessary, the alloy contains rare earth elements in a content between 0.0010 and 0.015 mass%. Rare earth elements capture sulfur and residual oxygen. Rare earth elements improve resistance to high-temperature cracking when welding base metals that have a residual S+O content higher than the filler wire. However, at content greater than 0.015%, eutectic phase precipitation at low melting points is enhanced, especially in the presence of silicon, resulting in loss of ductility and increased susceptibility to high-temperature cracking.

[0069] The rare earth elements are preferably selected from yttrium, cerium, and lanthanum, or from mixtures of the said elements.

[0070] According to one embodiment, the rare earth element is yttrium. In such a case, the alloy contains yttrium between 0.0010 and 0.015 mass%.

[0071] In one modified example, the rare earth elements consist of a mixture of cerium and lanthanum. In such a case, the Ce+La content in the alloy is between 0.0010 and 0.015 mass%.

[0072] In the presence of rare earths with a content ranging from 0.0010 to 0.015% by mass, the silicon content is limited to 0.25% by mass, preferably 0.20% by mass. Thus, in such cases, the silicon content ranges from 0.01 to 0.25% by mass, preferably from 0.01 to 0.20% by mass. In fact, silicon enhances the formation of the phase containing rare earths, and as a result, the possibility that rare earths capture residual sulfur and oxygen is reduced.

[0073] The alloy according to the invention has a yield strength Rp ranging from 500 MPa to 600 MPa 0.2 and a KCV toughness greater than or equal to 100 J / cm 2 and can be used to obtain a weld with ductility showing an overmatch in mechanical properties compared to a base material made of X56, X60, X65, or X70 steel.

[0074] As described above, the steel grades X56, X60, X65, X70, or X80 are defined in the API Specification 5L document, 45th edition, December 2012 of the American Petroleum Institute.

[0075] Furthermore, the alloy according to the invention - has good resistance to corrosion, especially resistance to local corrosion greater than or equal to that of the Inconel® 625 alloy of the comparative example, - has a weldability greater than or equal to that of the Inconel® 625 alloy of the comparative example and has.

[0076] Thereby, the characteristics of longitudinal and / or orbital welding are negligible with respect to the design of the welded joint designed to have a yield strength Rp greater than or equal to 500 MPa 0.2 and a KCV toughness greater than or equal to 100 J / cm 2 and especially including X56, X60, X65, and X70 steel as the base material.

[0077] Therefore, considering its properties, the alloy according to the present invention is particularly suitable for use as a filler material for manufacturing pipeline tubes intended for the transport of oil or gas, and suitable for laying at high formation rates, especially at depths lower than about 3,000 m, particularly in the deep sea of ​​the high seas, and especially at speeds of about 2 km / day.

[0078] Therefore, such alloys can be advantageously used as filler materials for longitudinal and / or orbital welding of pipeline tubes made from X56, X60, X65, or X70 steel, and intended to be laid to considerable depths, for example, less than 3,000 m, and at high laying speeds.

[0079] Since the alloy exhibits good corrosion resistance, it can also be used to produce internal coatings intended to improve the corrosion resistance of such tubes.

[0080] The alloy according to the present invention can be obtained by any suitable method known to those skilled in the art.

[0081] For example, in the first step, the starting material is supplied into an electric arc furnace. The starting material is selected to obtain an alloy containing less than 1.0 mass% iron. The above is a new material in particular. The starting material is then melted in the electric arc furnace and then subjected to a vacuum oxygen decarburization (VOD) method by a conventional method. - Decarburization method by oxygen injection and vacuum pump delivery (at a rate of several mbar), - Deoxidation and desulfurization under lime slag, and - Control of reducing elements such as Ti and Al This is done to obtain...

[0082] The present invention further relates to a filler wire made of an alloy having the above-described composition.

[0083] Such filler wires are particularly suitable for use in TIG or plasma welding processes, or MIG / MAG welding processes.

[0084] For example, a welding wire is - A welding filler wire made of a base material for welding two parts of a component together, wherein the base material is an iron-nickel alloy such as Fe-9Ni, i.e., containing nickel in a content between 5% and 10% by mass, or a nickel alloy such as C-276, C-4 or 22, or carbon steel, particularly X56, X60, X65 or X70 steel, as a filler wire and / or - A hard-facing wire made of a base material, particularly for producing a coating on a part or a portion of a part, wherein the base material is carbon steel, particularly X56, X60, X65, or X70 steel. It is intended to be used.

[0085] Alloy C-276 is specified in Table 1 of AWS A5.14 / A5.14M: 2018 (Specification for Nickel and Nickel-Alloy bare Welding Electrodes and rods) under the AWS classification reference ERNiCrMo-4 (number UNS N10276), with the title "Chemical composition requirements for Nickel and Nickel-Alloy Electrodes and Rods".

[0086] Alloy C-4 is defined in Table 1 of the standard AWS A5.14 / A5.14M: 2018 (Specification for Nickel and Nickel-Alloy bare Welding Electrodes and rods), under the AWS classification reference ERNiCrMo-7 (number UNS N06455), with the title "Chemical composition requirements for Nickel and Nickel-Alloy Electrodes and Rods".

[0087] Alloy 22 is specified in Table 1 of AWS A5.14 / A5.14M: 2018 (Specification for Nickel and Nickel-Alloy bare Welding Electrodes and rods) under the AWS classification reference ERNiCrMo-10 (number UNS N06022), with the title "Chemical composition requirements for Nickel and Nickel-Alloy Electrodes and Rods".

[0088] The component or part of the component is, in particular, a tube section, a tube and / or a metal sheet or a part of a metal sheet made of a base material.

[0089] For example, filler wires are also intended to be used as filler wires in metal addition manufacturing processes.

[0090] Additive manufacturing processes are those that use, for example, electric arcs, laser beams, and / or electron beams as energy sources to melt filler wires.

[0091] The additive manufacturing process is, in particular, the directed energy deposition additive manufacturing process. In such a process, the filler material is deposited, in particular through a nozzle, and immediately melted by concentrated thermal energy, in particular by a laser beam, electron beam, and / or electric arc.

[0092] For example, additive manufacturing processes include wire-arc (WAAM or "wire arc additive manufacturing"), wire-laser, electron beam-wire ("electron beam free-form fabrication" or "electron beam additive manufacturing") processes, or hybrid additive manufacturing processes that combine wire-arc and laser-powder technology or wire-arc and wire-laser technology.

[0093] In hybrid wire-arc and laser-powder processes, the powder used has the same composition as the wire.

[0094] Powders having a particle size distribution between 20 μm and 150 μm after screening can be obtained, for example, from a filler wire according to the present invention using plasma spraying technology. Preferably, the filler wire used to produce the powder has a diameter of about 3 mm.

[0095] The particle size distribution of the powder is determined, in particular, by the following measurement method. A powder batch is separated into multiple powder size distributions using an ultrasonic vibrating stainless steel screen. Analysis of the powder size distribution obtained from the screening is performed according to the ASTM B214-07 standard. The screening is used to obtain five size classifications: <20 μm - 20 μm to 45 μm - 45 μm to 75 μm - 75 μm to 105 μm - >105 μm.

[0096] The plasma spraying technique for producing powder from wire is publicly known and therefore will not be described in further detail.

[0097] The components or parts are particularly intended for the aerospace, transport, or energy markets. The components or parts form, for example, cases, frames, complexly shaped tubes, valves, mounting lugs, or parts of components having a specific function. As an example, such a part forms a heat exchange element containing channels for fluid circulation, formed, for example, by additive manufacturing on a support component, which is, for example, made of a different material from the heat exchange element.

[0098] The present invention further relates to a method for producing a filler wire made of the above-mentioned alloy.

[0099] The method includes, in a first step, supplying a semi-finished product made of the alloy. For this purpose, the alloy is cast into an ingot or directly into a billet, particularly using continuous casting, especially rotary casting. Thus, the semi-finished product obtained at the end of such a step is advantageously an ingot or a billet, having a diameter of, for example, between 130 and 230 mm, more specifically equal to about 150 mm.

[0100] Next, the semi-finished product is transformed by high-temperature conversion to form an intermediate wire.

[0101] In particular, during the high-temperature conversion process, semi-finished products, i.e., ingots or billets in particular, are heated to temperatures between 1180°C and 1220°C, especially in a gas furnace.

[0102] Next, these are subjected to high-temperature roughening to reduce their cross-section, for example, by giving the semi-finished product a square cross-section with sides of approximately 100 mm to 200 mm. A semi-finished product with a reduced cross-section is obtained therefrom. The length of the semi-finished product with a reduced cross-section is particularly between 10 and 20 meters.

[0103] Next, the semi-finished product with reduced cross-section is subjected to high-temperature conversion again at temperatures between 1050 and 1150°C to obtain intermediate wire. The intermediate wire is, in particular, machine wire. The wire has approximately equal diameters, particularly 5.5 mm, which range from, for example, 5 mm to 21 mm. Advantageously, during such a process, the intermediate wire is produced by hot rolling in a wire mill train.

[0104] Next, if necessary, the intermediate wire is subjected to heat treatment in a gas furnace at a temperature between 1150°C and 1220°C for a duration between 60 and 120 minutes, followed by hyperquenching in a pool.

[0105] Next, the intermediate wire is washed with acid, and then wound onto a coil.

[0106] If necessary, to obtain a filler wire, the intermediate wire thus obtained is drawn using a known type of wire drawing equipment. The filler wire has a diameter smaller than the diameter of the starting wire. Its diameter is particularly between 0.5 mm and 3.5 mm. Its diameter is advantageously between 0.8 mm and 2.4 mm.

[0107] The wire stretching process includes one or more wire stretching passes, depending on the final diameter to be achieved, and preferably involves annealing between two consecutive wire stretching passes. Annealing is carried out, for example, while passing through a reducing atmosphere at a temperature of about 1150°C.

[0108] The wire stretching process is preferably followed by cleaning the surface of the stretched wire, and then winding the wire.

[0109] The wire stretching path is a cold path.

[0110] Any other method for producing the alloy according to the present invention, and any other method for producing a finished product made of an alloy known to those skilled in the art, can be used for this purpose.

[0111] The present invention further relates to a welded assembly 1 comprising at least two parts of a component 3 made of a base metal, joined together by welding beads 5 obtained from the aforementioned filler wire. The aforementioned welded assembly is schematically shown in Figure 1.

[0112] The dilution of the wire during welding ranges from, for example, 1% to 10%, and is particularly close to 5%.

[0113] Throughout the text, “parts of a part” welded together refers to both cases: when the welded parts belong to two separate parts, and when the parts are two parts of the same part folded over itself, for example, two longitudinal edges of sheet metal welded together to form a tube.

[0114] Base metals include, in particular, carbon steels such as X56, X60, X65, or X70 steel, or iron-nickel alloys such as Fe-9%Ni, i.e., those having a nickel content between 5 and 10% by mass, or nickel alloys such as C-276, C-4, or C-22.

[0115] The present invention further relates to a welding method for welding together at least two parts of a component 3, which are made of the base metals defined above, to produce a welded assembly 5 as illustrated in Figure 1.

[0116] In the first step, the aforementioned filler wire is provided. A portion of part 12 made of a base metal, which will be welded together by the welding process, is also provided.

[0117] Next, the parts of component 12 are welded together using a filler wire as the welding wire. In such a process, butt welding is preferably performed.

[0118] The welding process may include one or more welding passes. Conventionally, the welding process includes a first welding pass called a root pass, and one or more subsequent additional welding passes called filler passes. All welding passes are performed by using the filler wire according to the present invention described above. Therefore, dilution of the filler wire is limited to dilution with molten base metal obtained from the welding.

[0119] The dilution of the wire during welding ranges from, for example, 1% to 10%, and is particularly close to 5%.

[0120] Welding is performed, for example, by arc welding, by plasma welding using a filler wire, by MIG (metal-inert gas) welding, or by MIG / MAG (metal-active gas) welding.

[0121] According to one embodiment, as shown in Figure 2, the welded assembly 1 is a tube section 7 including a sheet metal 9 folded into the shape of a tube, the longitudinal edges 12 of which are joined together by welding beads 15 obtained from a filler wire as defined above. In such a case, the portion of part 3 includes the longitudinal edges 12 of the sheet metal 9.

[0122] The walls of tube section 5 have a thickness that, for example, ranges from 3 mm to 60 mm.

[0123] Tube section 5 is specifically intended for transporting corrosive products, more specifically gas or oil. More specifically, it is intended to form a component of a pipeline, particularly laid on the seabed, more specifically to depths of approximately 3,000 m.

[0124] A further subject of the present invention is a method for manufacturing such a tube section 5.

[0125] The method includes the step of providing a sheet metal 9 made of a base metal. Such a sheet metal 9 is shown in Figure 3. The sheet metal 9 extends along a longitudinal direction L and has a longitudinal edge 12 substantially parallel to the longitudinal direction L. For example, the sheet metal has a thickness that ranges from 3 mm to 60 mm.

[0126] The method further includes the steps of folding the sheet metal 9 so that two longitudinal edges 12 face each other, and then welding the two longitudinal edges 12 face each other using the welding method defined above. In such a case, the portion of part 3 described in the context of the welding process includes the longitudinal edges 12 of the sheet metal 9.

[0127] The welds produced during such processes are longitudinal welds. Preferably, the welds are butt welds.

[0128] At the end of such a process, a tube section 7 is obtained as shown in Figure 2. The sheet metal 9 is folded into the shape of a tube, and the longitudinal edges 12 of the sheet metal 9 are joined together by welding beads 15 obtained from the filler wire defined above.

[0129] In another embodiment, as shown in Figure 4, the welded assembly is a tube 20, and the portion of part 3 is a tube section 7 connected together by welding beads 22 obtained from the filler wire defined above. In such an embodiment, the welding beads 22 extend along the circumference of the tube 20 to connect the tube section 7 together.

[0130] The weld is, in particular, a butt weld, and preferably an orbital weld. Orbital welding refers to a weld produced by rotating the welding tool, i.e., more specifically, the welding torch, relative to the tube section 7 to be welded.

[0131] The wall 20 has a thickness that is, for example, between 3 mm and 60 mm.

[0132] According to one embodiment, the tube section 7 is the tube section described above.

[0133] In a modified version, part 3 is a tube section that does not include any longitudinal welds and is obtained, for example, by billet extrusion.

[0134] Tube 20 is intended in particular to transport corrosive products, more specifically gas or oil. More specifically, it is intended to form a pipeline component, and to be laid, especially on the seabed, to depths of approximately 3,000 m.

[0135] Therefore, a further subject of the present invention is a method for manufacturing the tube 20 as defined above.

[0136] During such a process, at least two tube sections 7 are provided. Each tube section 5 is substantially cylindrical and has an axis M and two longitudinal ends 24 spaced apart along the direction of the axis M.

[0137] Next, the two tube sections 7 are positioned in such a manner that their longitudinal ends 24 face each other along the direction of the axis M of the tube sections, and then the longitudinal ends 24 facing the two tube sections 7 are welded together using the welding method defined above. In such a case, the portion of the part 3 defined in the context of the welding process includes the longitudinal ends 24 of the tube sections 7.

[0138] Advantageously, during such a process, a butt weld is formed between the longitudinal ends 24 facing the tube section 7. The weld is preferably an orbital weld.

[0139] Preferably, the welding process includes machining chamfers on the ends 24 of the tube sections 7 that will be welded together, before joining the tube sections 7 together.

[0140] The welding process is carried out in a number of times equal to the number of tube sections 7 to be welded to form the tube 20 minus one.

[0141] In one embodiment, the tube section 7 is the tube section 7 described above.

[0142] In modified examples, the method can be carried out with any type of tube section whose longitudinal ends are made of a base metal, regardless of the method used to obtain the tube section. More specifically, the method is carried out with a tube section that does not include longitudinal welds and is obtained by billet extrusion.

[0143] The method, in more detail, is carried out on a barge positioned at the location where the tube 20 will be installed.

[0144] At the end of the welding process, a tube 20 is obtained. The tube 20 includes at least two consecutive tube sections 7 assembled together by welding beads 22 produced from the filler wires defined above.

[0145] The present invention further relates to a coated part 26 shown in Figure 5, which includes a substrate 28 made of a base material coated with a coating 30 made of the alloy described above. The base material is a metallic material.

[0146] The base material is, in particular, carbon steel. Preferably, the base material is X56, X60, X65, or X70 steel.

[0147] The coating 30 is applied to the substrate 28 by a hardening process, which involves welding using a filler wire having the composition described above.

[0148] The coating 30 has a thickness that is more specifically between 2 mm and 20 mm.

[0149] Such a coating 30 improves the resistance of the coated part 26 to corrosion, more specifically in the presence of corrosive products such as petroleum products.

[0150] The coated component 26 is, in particular, a coated tube section 7, where the coating 30 is formed on the inner wall of the tube section 7 and covers the inner wall of the tube section 7 over its entire surface, including, in particular, welding beads 12 if present.

[0151] The present invention further relates to a method for producing the above-described coated part 26, comprising the steps of: providing a substrate 28 made of a base material; and subsequently depositing a coating 30 onto the surface of the substrate by a welding hardening process using a filler wire having the above-described composition.

[0152] If the coated part 26 is a section of the coated tube 7, the manufacturing method more specifically includes the steps of manufacturing the tube section 7 by implementing the method described above, and subsequently adhering the coating 30 to the inner surface of the tube section 7 by a hardening process by welding using a filler wire having the composition described above.

[0153] The coating 30 improves the resistance of the tube section 7 to corrosion, for example, during the transportation of easily variable and corrosive petroleum products.

[0154] According to a particular embodiment, the tube 20 described above includes two tube sections 7 coated with the coating 30 described above, which are joined together by welding beads 22.

[0155] The present invention further provides a method for manufacturing a component 40 schematically shown in Figure 6, which is made of the alloy described above, - A process of supplying a filler wire made of alloy, - A step of manufacturing part 40 by a metal addition process using a filler wire and / or powder made of the above-mentioned alloy as the filler material. This includes methods.

[0156] Additive manufacturing processes are those that use, for example, electric arcs, laser beams, and / or electron beams as energy sources to melt the filler material.

[0157] Additive manufacturing processes, in particular, are directed energy deposition additive manufacturing processes. In such processes, the filler material is deposited, in particular through a nozzle, and immediately melted by concentrated thermal energy, in particular by a laser beam, electron beam, and / or electric arc.

[0158] For example, additive manufacturing processes include wire-arc, wire-laser, electron beam-wire ("electron beam free-form fabrication") processes, or hybrid additive manufacturing processes combining wire-arc and laser-powder technology or wire-arc and wire-laser.

[0159] When a hybrid additive manufacturing process is used that combines wire-arc and laser-powder technology or wire-arc and wire-laser technology, the powder and filler wire are made from the alloys described above.

[0160] The additive manufacturing process described above is publicly known and therefore will not be described in detail.

[0161] If the filler material includes powder, particularly in the context of hybrid wire-arc and laser-powder processes, the process further includes a step of supplying powder made of the alloy described above before the production of part 40. The powder, having a particle size distribution between 20 μm and 150 μm after screening, is produced, for example, by plasma spraying from a wire made of the alloy described above, more specifically a wire having a diameter of about 3 mm.

[0162] The plasma spraying process is publicly known and therefore will not be described in detail.

[0163] The present invention also relates to a part 40 or a portion of a part made of the above-mentioned alloy produced by metal addition manufacturing.

[0164] The metal addition process, in more detail, uses a filler wire and / or powder made from the aforementioned alloy as filler material.

[0165] Additive manufacturing processes are those that use, for example, electric arcs, laser beams, and / or electron beams as energy sources to melt the filler material.

[0166] Additive manufacturing processes, in particular, are directed energy deposition additive manufacturing processes. In such processes, the filler material is deposited, in particular through a nozzle, and immediately melted by concentrated thermal energy, in particular by a laser beam, electron beam, and / or electric arc.

[0167] For example, additive manufacturing processes include wire-arc, wire-laser, electron beam-wire ("electron beam free-form fabrication") processes, or hybrid additive manufacturing processes combining wire-arc and laser-powder technology or wire-arc and wire-laser.

[0168] When a hybrid additive manufacturing process is used that combines wire-arc and laser-powder technology or wire-arc and wire-laser technology, the powder and filler wire are made from the alloys described above.

[0169] Parts or parts obtained by the metal addition process, such as part 40, remain solidified. Therefore, the part or part has a solidified microstructure typical of a possible nickel alloy, such a microstructure typically containing columnar dendrites epitaxially growing on each other, the orientation of which depends on the width of the resulting metal wall. Furthermore, parts obtained by the addition process have a series of overlapping solidified layers due to that process. Each layer obtained by the solidification of deposited molten metal droplets melts the skin of the preceding layer and subsequently heats the remainder of the layer below to create metallurgical continuity. The reheating temperature is all low because the layer in question is away from the zone undergoing melting and solidification. Such specific microstructures can be observed by metallographic observation of the metallographic section of the part.

[0170] Therefore, parts 40 or parts produced by the metal addition process can be distinguished from parts produced by other methods, and in particular from parts produced by conventional metallurgy that produce a recrystallized structure with homogeneous grains.

[0171] Parts 40 or parts of parts are intended in particular for the aerospace, transport, or energy markets. Parts or parts of parts form, for example, cases, frames, tubes with complex shapes, valves, mounting lugs, or parts of parts having a specific function. As an example, a part of such a part forms a heat exchange element including channels for fluid circulation, formed, for example, by additive manufacturing on a support part, which is made of a different material from the material of the heat exchange element.

[0172] test In the first series of tests, the inventors performed laboratory casting to produce ingots containing an alloy having the composition specified above, as well as a comparative alloy having a different composition from the above-mentioned composition.

[0173] The alloy was produced under vacuum, and the resulting ingot was transformed by hot rolling to obtain a sheet bar with dimensions of 10 × 50 × 300 mm.

[0174] The alloy compositions of the tested sheet rods are shown in Table 1 (Table 2) below.

[0175] Next, the inventors conducted the following tests on the sheet rods produced in this manner.

[0176] In some sheet rods, the inventors used a TIG torch to create joint fusion lines back and forth in order to generate a solidified structure with a sheet rod thickness equivalent to that produced by TIG or MIG welding under non-dilution conditions, and sampled tensile and elastic test specimens from the molten region.

[0177] Next, the inventors carried out the following: - The above tensile test specimen, conforming to standard NF EN ISO 6892-1 (December 2019), showed an elongation of 0.2% at 20°C (Rp 0.2 Mechanical flat tensile test at room temperature (20°C) to measure yield strength. The test results are shown in Table 2 (Table 3) below under "Rp 0.2 Summarize in the "" column. - Elasticity testing at room temperature (20°C) on the aforementioned elastic test specimen, along with measurement of impact fracture energy (indicated as KCV) according to standard NF EN ISO 148-1 (January 2011). Fracture energy is expressed in J / cm². 2 It is expressed in units of kCV. The fracture energy reflects the elasticity of the part. The test results are summarized in the "KCV" column of Table 2 (Table 3) below.

[0178] The inventors also measure the surface percentage of the phase precipitated during solidification of the molten metal under the passage of a TIG torch in the melting zone of the sheet rod. The surface percentage of the precipitated phase is determined by image analysis of the sheet rod image obtained with a scanning electron microscope (SEM). In fact, the precipitated phase corresponds to the white area in the image and is detected by image processing software that detects the white area using grayscale analysis and then determines the surface percentage occupied by the white area. The measurement results are summarized in the "FS" column of Table 2 (Table 3) below.

[0179] The inventors also conducted a Varestraint test according to European standard FD CEN ISO / TR 17641-3 (November 2005) under 3.2% plastic deformation in relation to sheet rods not used in bonding and fusion lines, in order to measure the total length of cracks generated during the test and to evaluate their resistance to high-temperature cracks. The test results are shown in Table 2 (Table 3) below under "L 合計 Let's summarize this under "cracks".

[0180] Finally, the inventors conducted a potentiometric titration test to assess the alloy's resistance to localized corrosion. For this purpose, they used 11.9 mol.l at pH 5.4 and a temperature of 30°C. -1 The pitting potential V in a LiCl medium was measured, and this pitting potential was compared to the pitting potential (V) of Inconel® 625. Inconel 625 / SCE Compared to <120mV), where SCE is the reference potential for the saturated calomel electrode.

[0181] In Tables 1 (Table 2) and 2 (Table 3) below, tests that do not conform to the present invention are underlined.

[0182] [Table 2A]

[0183] [Table 2B]

[0184] In the alloys shown in Table 1 (Table 2), the Al content is between 0.01% and 0.35%, the N content is between 0.001% and 0.05%, the Mg and Ca content is less than or equal to 0.005%, and the P content is less than or equal to 0.005%. Furthermore, the alloys do not contain niobium.

[0185] Regarding the alloys in Table 1 (Table 2), the remainder consists of nickel and impurities resulting from the manufacturing process.

[0186] Furthermore, all compositions are expressed as mass percentages.

[0187] [Table 3A]

[0188] [Table 3B]

[0189] Furthermore, during potentiometric titration tests, alloys A1 to A28 in Table 1 (Table 2) generated pitting potentials V greater than or equal to 150 mV relative to the reference potential for a saturated calomel electrode. Therefore, these alloys exhibit better resistance to localized corrosion than Inconel® 625 alloys.

[0190] As described above, preferably, the following properties: - Yield strength Rp greater than or equal to 500 MPa 0.2 , - 100 J / cm 2 KCV elasticity greater than or equal to that, - Total length of cracks less than or equal to 20 mm, - Surface percentage of precipitated phase FS less than or equal to 1.5%, - Resistance to localized corrosion greater than or equal to that of Inconel® 625 alloy. However, they are combined to arrive at the desired result.

[0191] Among the parameters listed above, the total crack length represents the weldability of the alloy. Since the total crack length for Inconel® 625 alloy is equal to 20 mm, a total crack length of less than or equal to 20 mm corresponds to a weldability greater than or equal to that of Inconel® 625 alloy, and is therefore satisfactory for the application being considered.

[0192] Such properties were obtained in Examples A2 to A4, A8 to A11, A14 to A16, A19 to A21, A25 and A26, which correspond to alloys having the above-mentioned compositions.

[0193] On the other hand, yield strength Rp 0.2 In the case of Comparative Examples A1, A7, A18, and A24, the KCV elasticity is less than or equal to 500 MPa, but the KCV elasticity is insufficient, and / or the crack length is too long in the case of Comparative Examples A5, A6, A12, A13, A17, A22, A23, A27, and A28. Note that in the context of counterexamples, the relationship -0.5 × (Cr + Fe) + 25% ≤ Mo + W ≤ -0.5 × (Cr + Fe) + 30% is not satisfied.

[0194] Furthermore, as shown by Comparative Examples A6, A13, A17, A23, and A28, alloys containing iron at a content greater than 1.0% exhibit degraded ductility and increased susceptibility to high-temperature cracking.

[0195] Generally, the inventors believe that a surface percentage of the precipitated phase FS greater than 1.5% is 100 J / cm². 2 We found that this resulted in KCV elasticity of less than 20 mm and / or crack lengths greater than 20 mm.

[0196] The inventors also conducted a second series of tests under the same conditions as described for the first series of tests, but with the sheet rods being made of an alloy having the composition summarized in Table 3 (Table 4). Furthermore, the results of the tests conducted on the sheet rods are shown in Table 4 (Table 5).

[0197] [Table 4]

[0198] In the alloys shown in Table 3 (Table 4), the Al content is between 0.01% and 0.35%, the N content is between 0.001% and 0.05%, the Mg and Ca content is less than or equal to 0.005%, and the P content is less than or equal to 0.005%. Furthermore, the alloys do not contain niobium.

[0199] For all the alloys in Table 3 (Table 4), the remainder consists of nickel and impurities resulting from the manufacturing process.

[0200] Furthermore, all compositions are expressed as mass percentages.

[0201] [Table 5A]

[0202] [Table 5B]

[0203] Furthermore, during potentiometric titration tests, alloys B1 to B28 in Table 3 (Table 4) generated pitting potentials V greater than or equal to 150 mV relative to the reference potential for a saturated calomel electrode. Therefore, these alloys exhibit better resistance to localized corrosion than Inconel® 625 alloys.

[0204] Therefore, it was found that the desired properties regarding yield strength, elasticity, weldability, surface percentage of precipitated phase, and resistance to local corrosion were obtained in Examples B2 to B4, B8 to B11, B14 to B16, B19 to B21, B25 and B26, which correspond to alloys having the above-described compositions.

[0205] For other results, please refer to the conclusions drawn from Table 2 (Table 3).

[0206] In detail, yield strength Rp 0.2 In the case of Comparative Examples B1, B7, B18, and B24, the elasticity is less than or equal to 500 MPa, while the KCV elasticity is insufficient in the case of Comparative Examples B5, B6, B12, B13, B17, B22, B23, B27, and B28. Note that in the context of counterexamples, the relationship -0.5 × (Cr + Fe) + 25% ≤ Mo + W ≤ -0.5 × (Cr + Fe) + 30% is not satisfied.

[0207] Furthermore, weldability and elasticity deteriorate when the alloy contains more than 1.0% iron.

[0208] Therefore, by further comparing the results in Tables 2 (Table 3) and Table 4 (Table 5), it can be seen that the addition of rare earth elements improves the alloy's resistance to high-temperature cracking.

[0209] The addition of rare earth elements is particularly advantageous when the base metal to be welded has a higher sulfur and / or oxygen content than the filler wire. In fact, the inventors have found that rare earth elements contribute to the deoxidation and / or desulfurization of the molten pool during welding operations, and therefore contribute to improved resistance to high-temperature cracks.

[0210] The alloy according to the present invention has a yield strength Rp greater than or equal to 500 MPa. 0.2 And, 100 J / cm 2 These alloys have a KCV elasticity greater than or equal to that of alloys X56, X60, X65, and X70, etc., and have a yield strength of less than 500 MPa Rp 0.2 It can be used to obtain an overmatch in mechanical properties for base metals. Therefore, the characteristics of the weld can be ignored with respect to the design of welded assemblies made of alloys such as the base material.

[0211] Furthermore, the alloy presents the following: - Corrosion resistance greater than or equal to that of comparative Inconel® 625 alloy. - Weldability greater than or equal to that of comparative Inconel® 625 alloy.

[0212] Therefore, considering its properties, the alloy according to the present invention is particularly suitable as a filler material for manufacturing pipeline tubes intended for the transport of oil or gas, and suitable for high formation rates in offshore deep seas, especially at depths of up to about 3,000 m, and particularly suitable for laying at a rate of about 2 km / day.

[0213] Due to its favorable properties, the alloy according to the present invention can also be advantageously used in the context of the parts described above. [Explanation of symbols]

[0214] 1. Welded Assembly 3 parts 5 Welding beads 7 Tube Sections 9 Sheet metal 12. Vertical edges 15 Welding Beads 20 tubes 22 Welding Beads 24. Vertical ends 26 Coated parts 28 Base material 30 Coating 40 parts

Claims

1. Composition by weight: 16.5%≦Cr≦25.0% 11.0%≦Mo≦18.0% 2.0%≦W≦7.0% Fe≦1.0% Mo+W≦−0.5×(Cr+Fe)+30%, where Mo is the molybdenum content of the alloy in wt.%, W is the tungsten content of the alloy in wt.%, Cr is the chromium content of the alloy in wt.%, and Fe is the iron content of the alloy in wt.%. Mo+W≧−0.5×(Cr+Fe)+25%, where Mo is the molybdenum content of the alloy in wt.%, W is the tungsten content of the alloy in wt.%, Cr is the chromium content of the alloy in wt.%, and Fe is the iron content of the alloy in wt.%. Ti+Ta≦0.80%, where Ti is the titanium content in the alloy in wt.% and Ta is the tantalum content in the alloy in wt.% 0.01%≦Si≦0.75% 0.01%≦Al≦0.35% 0.01%≦Mn≦0.35% Ca≦0.005% Mg≦0.005% Nb≦0.01% 0.001%≦C≦0.05% 0.001%≦N≦0.05% S≦0.003% P≦0.005%, 0.0010%≦Rare Earth≦0.015% as required having a silicon content of less than or equal to 0.25% in the presence of rare earths with a content comprised between 0.0010% and 0.015%; An alloy having a nickel content greater than or equal to 54%, the remainder being nickel and unavoidable impurities resulting from production.

2. 2. The alloy of claim 1, wherein the iron content is less than or equal to 0.5%.

3. 3. The alloy of claim 1 or 2, wherein the rare earth is selected from yttrium, cerium, and lanthanum, and mixtures thereof.

4. 4. The alloy of claim 3, wherein the rare earth is selected from yttrium or a mixture of cerium and lanthanum.

5. 10. A coated component (26) comprising a substrate (28) made of a base material and a coating (30) made of an alloy according to any one of claims 1 to 4, wherein the base material is a metallic material.

6. 6. The coated part of claim 5, wherein the coated part (26) is a tube section (7).

7. A filler wire made of an alloy having a composition according to any one of claims 1 to 4.

8. 8. A method of manufacturing a filler wire as claimed in claim 7, comprising the steps of: - providing a semi-finished product consisting of an alloy according to any one of claims 1 to 4; - high temperature conversion of the semi-finished product in order to reduce the diameter of the semi-finished product to form an intermediate wire; - converting the intermediate wire into a filler wire having a smaller diameter than the intermediate wire, the process including a drawing step; A manufacturing method comprising:

9. 1. A welded assembly (1; 7; 20) comprising at least two parts (3; 12; 7) of a part, each of the two parts of the part consisting of a base material, the parts (3; 12; 7) of the part being joined together by a weld bead (5; 15; 22) obtained from a filler wire according to claim 7, the base material being selected from an iron-nickel alloy, a nickel alloy and carbon steel.

10. 10. The welded assembly according to claim 9, wherein the welded assembly forms a tube section (7) comprising sheet metal bent into the shape of a tube, the longitudinal edges (12) of which form the portions (3) of the components joined together by weld beads (15).

11. 11. A welded assembly according to claim 10, wherein the tube section (7) is provided on at least a portion of its inner surface with a coating (30) consisting of an alloy according to any one of claims 1 to 4.

12. 10. The welded assembly of claim 9, wherein the welded assembly forms a tube (20) including at least two tube sections (7), the tube sections (7) forming portions (3) of a component, and the weld bead (22) extending around a circumference of the tube (20).

13. A method for producing a welded assembly (1; 7; 20) according to any one of claims 9 to 12, comprising the step of welding together two parts (3; 12.7) of a component using a filler wire according to claim 7.

14. A method for producing a welded assembly (7) according to claim 10 or 11, wherein the welding step is a step of welding together the longitudinal edges (12) of the metal sheets (9).

15. 13. A method for producing a welded assembly (20) according to claim 12, comprising, prior to the welding step, the following sequential steps: - providing a first tube section (7) and a second tube section (7), each extending along a longitudinal axis (M) and made of a base material; - positioning the first and second tube sections (7) such that a longitudinal end (24) of the first tube section (7) faces a longitudinal end (24) of the second tube section (7) along a longitudinal axis (M) of the first and second tube sections (7); Including, the welding step being a step of welding together the two longitudinal ends (24) facing the first and second tube sections (7); method.

16. 5. A component or part of a component made of an alloy according to any one of claims 1 to 4.

17. The part or portion of a part of claim 16, wherein the part or portion of a part comprises a series of overlapping solidified layers.

18. 5. A method of manufacturing a component or part of a component, comprising manufacturing the component or part of a component by a metal additive manufacturing process using as filler material a filler wire comprising the alloy of any one of claims 1 to 4 and / or a powder comprising the alloy of any one of claims 1 to 4.

19. Use of the filler wire according to claim 7, as a welding filler wire for welding together two parts of a part, the base material being an iron-nickel alloy, a nickel alloy or carbon steel; and / or as a hardfacing wire for producing a coating on a component or part of a component, consisting of a base material which is a metallic material; and / or - As a filler wire in metal additive manufacturing processes, use.

20. A metal powder consisting of an alloy according to any one of claims 1 to 4.

21. 21. A method of producing the metal powder of claim 20, comprising the steps of providing a filler wire of claim 7 and plasma spraying the filler wire to obtain a metal powder.